Plausible mechanisms in the pathobiology of acantholytic squamous cell carcinoma: An evidence based hypothesis. (October 2022) - Krishnan, Reshma Poothakulath; Ramani, Pratibha; Pandiar, Deepak
Abstract: Oral squamous cell carcinoma is the most common malignant neoplasm arising from the oral epithelium. Despite advances in the diagnosis and treatment modalities the patient outcome has not improved vastly. Among the various histological variants, acantholytic squamous cell carcinoma is a rare yet an aggressive subtype with poorer prognosis. There is dearth in information regarding the data pertaining to the pathogenesis of acantholysis in this variant. Thus, in the present paper we made an attempt to explain the pathobiology of acantholysis in oral acantholytic squamous cell carcinoma in purview of acantholysis, resistance to anoikis and collective cell migration. We opine that the characteristic histomorphological appearance of ASCC could be attributable to a temporal interplay between the factors mentioned above which may further dictate the grave outcome of this rare variant of oral squamous cell carcinoma.